Ursolic acid inhibits the initiation, progression of prostate cancer and prolongs the survival of TRAMP mice by modulating pro-inflammatory pathways - Shanmugam, M.; Ong, T.; Kumar, Alan Prem; Lun, C.; Ho, P.; Wong, P.; Hui, K.; Sethi, G. (Public Library of Science, 2012)
Prostate cancer is one of the leading causes of cancer death among men worldwide. In this study, using transgenic adenocarcinoma of mouse prostate (TRAMP) mice, the effect of diet enriched with 1% w/w ursolic acid (UA) was investigated to evaluate the stage specific chemopreventive activity against prostate cancer. We found that TRAMP mice fed with UA diet for 8 weeks (weeks 4 to 12) delayed formation of prostate intraepithelial neoplasia (PIN). Similarly, mice fed with UA diet for 6 weeks (weeks 12 to 18) inhibited progression of PIN to adenocarcinoma as determined by hematoxylin and eosin staining. Finally, TRAMP mice fed with UA diet for 12 weeks (weeks 24 to 36) demonstrated markedly reduced tumor growth without any significant effects on total body weight and prolonged overall survival. With respect to the molecular mechanism, we found that UA down-regulated activation of various pro-inflammatory mediators including, NF-?B, STAT3, AKT and IKKa/ß phosphorylation in the dorsolateral prostate (DLP) tissues that correlated with the reduction in serum levels of TNF-a and IL-6. In addition, UA significantly down-regulated the expression levels of cyclin D1 and COX-2 but up-regulated the levels of caspase-3 as revealed by immunohistochemical analysis of tumor tissue sections. Finally, UA was detected in serum samples obtained from various mice groups fed with enriched diet in nanogram quantity indicating that it is well absorbed in the GI tract. Overall, our findings provide strong evidence that UA can be an excellent agent for both the prevention and treatment of prostate cancer. © 2012 Shanmugam et al.